Characterization of the complete mitochondrial genome of Euspira gilva with phylogenetic analysis. Issue 2 (2nd April 2020) - Wang, Zongxing; Xu, Zongjun; Wang, Bo; Zheng, Fengrong; Chen, Wei; Zhou, Quanli
Abstract: Here, we determined the complete mitogenome sequence of Euspira gilva (Littorinimorpha: Naticidae). The complete mitochondrial genome is circular and 16, 119 bp in length, containing 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, and 22 transfer RNA genes. All PCGs and rRNA genes are encoded on the heavy strand while tRNA genes are distributed in both the strands. The overall nucleotides base composition of the heavy strand is A (31.80%), G (14.72%), C (13.72%), and T (39.76%), with an A + T bias (71.56%). All of the PCGs had ATG as their start codon. The common termination codon is TAA, except for nd4l terminated with TAG. The 22 tRNA genes could be folded into a typical clover-leaf secondary structure. As seen from the phylogenetic tree, E. gilva has a more close relationship with Neverita didyma and Glossaulax reiniana .